2003
DOI: 10.1021/la020849o
|View full text |Cite
|
Sign up to set email alerts
|

Structure of Phase-Separated Langmuir−Blodgett Films of Hydrogenated and Perfluorinated Carboxylic Acids Investigated by IR Spectroscopy, AFM, and FFM

Abstract: The structure of the mixed Langmuir and Langmuir-Blodgett (LB) films of arachidic acid (AA) and perfluorotetradecanoic acid (PA) are investigated. Surface pressure-area isotherms of the mixed Langmuir films of AA and PA fall between those of pure AA and pure PA, indicating that the additivity rule holds in this system. This shows that the two components are phase-separated or are ideally mixed. The results of transmission and reflection-absorption IR spectroscopic measurements of the mixed LB films reveal that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
70
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(74 citation statements)
references
References 32 publications
4
70
0
Order By: Relevance
“…Seoane et al [34] reported mixed films of cholesterol with saturated or unsaturated fatty acids, but these are not discussed here due to the peculiar characteristics of cholesterol. Several authors [23,[25][26][27]30,32] have also observed phase separation in fatty acid mixed monolayers of fluorinated and hydrogenated amphiphiles.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Seoane et al [34] reported mixed films of cholesterol with saturated or unsaturated fatty acids, but these are not discussed here due to the peculiar characteristics of cholesterol. Several authors [23,[25][26][27]30,32] have also observed phase separation in fatty acid mixed monolayers of fluorinated and hydrogenated amphiphiles.…”
Section: Discussionmentioning
confidence: 94%
“…One of the main aspects of these mixtures is the miscibility and phase separation. Recent articles on mixed fatty acids systems are those of [23][24][25][26][27][28][29][30][31][32]. Furthermore, since fatty acids or phospholipids usually present unsaturations in the hydrocarbon chains, the study of mixtures of saturated and unsaturated compounds is of interest.…”
Section: Introductionmentioning
confidence: 99%
“…Many of these applications originate from the improved thermal, chemical and physical properties of fluorine-terminated surfaces in comparison with their non-fluorinated counterparts, including low friction coefficients, chemical inertness [3][4][5] and high dielectric constant [6]. Of particular recent interest is the ability of fluorinated surfactants to phase-separate from hydrocarbon surfactants at the air-water and solid-air interface.…”
Section: Introductionmentioning
confidence: 99%
“…Of particular recent interest is the ability of fluorinated surfactants to phase-separate from hydrocarbon surfactants at the air-water and solid-air interface. Under appropriate conditions, fluorinated surfactants can phase-separate from hydrocarbon amphiphiles, forming monolayer films with well-defined surface domains [3,[7][8][9][10]. We believe that the controlled patterning of solid surfaces with fluorinated molecules has important technological applications in the field of chemical and biological sensing [11], and wish to both understand and control the mechanism of phase-separation in these mixed systems.…”
Section: Introductionmentioning
confidence: 99%
“…The π-A isotherms of mixed DACE/SA monolayer show steeper surface pressure-area curves and higher collapse pressures, compared to those of pure DACE monolayer. As the content of SA increases, the shape of the π-A isotherm [21,22]. The value of A ex can be expressed as:…”
Section: The Monolayer Behavior Of Dace/sa On the Air/water Interfacementioning
confidence: 99%